1992
DOI: 10.1002/mrd.1080320304
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the nuclear matrix at the transition from maternal to zygotic control of development in the mouse: An immunocytochemical study

Abstract: The nuclear matrix is thought to be responsible for DNA organization, DNA replication, RNA synthesis, and RNA processing. We have looked for the presence of nuclear matrix antigens during early mouse embryogenesis. Antibodies to peripheral and interior antigens (P1, Pl1, Pl2, and lamin B) were used to immunolocalize nuclear matrix antigens in germinal vesicle oocytes, metaphase II oocytes, zygotes, two-cell-stage embryos, and eight-cell stage embryos. All antibodies reacted with the nuclei of germinal vesicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Somatic histone H1 is not detected in early mouse embryos until the four-cell stage, in which its synthesis appears to be associated with progression through the S phase of the cell cycle (10). Data concerning the nuclear matrix in preimplantation embryos are extremely sparse, but immunocytochemical evidence suggests that a matrix is formed as early as the two-cell stage in mouse embryos (52). Taken together with these data, our results lend (Fig.…”
Section: Inspection Of the Results For Sar-lines Insupporting
confidence: 83%
“…Somatic histone H1 is not detected in early mouse embryos until the four-cell stage, in which its synthesis appears to be associated with progression through the S phase of the cell cycle (10). Data concerning the nuclear matrix in preimplantation embryos are extremely sparse, but immunocytochemical evidence suggests that a matrix is formed as early as the two-cell stage in mouse embryos (52). Taken together with these data, our results lend (Fig.…”
Section: Inspection Of the Results For Sar-lines Insupporting
confidence: 83%
“…The changes in 1CG organization are consistent with the EM localization of Sm and other snRNP antigens primarily in association with ICG and perichromatin fibrils [34,50,72]. Although the antigen detected by the PII antibody in the nucleoplasm is unknown, it is widely conserved [19,66], and its behaviour during lymphocyte activation [21,69], early embryogenesis [61] and mitosis [17] indicates that it carries out a transcription-related function. EM immunoperoxidase and immunogold labelling studies of 3T3 [22] and Heka (Chert and Cha[y, in preparation) cells have shown that, like snRNP antigens, the internal Pil component is associated with ICG clusters.…”
Section: Nuclear Matrixsupporting
confidence: 68%
“…Specifically, cycloheximide did not block the appearance of a specific snRNP epitope (Y12), while a-amanitin did block this appearance . Additional data (Prather and Schatten, unpublished) involving the construction of the nuclear matrix of the mouse embryo also showed that long-term treatment with cycloheximide did not block the appearance of some of the nuclear matrix antigens, while a-amanitin did block the developmental appearance of these antigens (Prather and Schatten, 1992). Thus, it appears that these developmental events were not blocked by cycloheximide, because the cycloheximide may no longer have been effective.…”
Section: Discussionmentioning
confidence: 97%